Fermentative production of value-added products from sorghum bran - Ahmed El-Imam, Amina (2017)
Studies were undertaken to investigate the potential for using sorghum bran from a traditional wet-milling process as a raw material for the fermentative production of value-added products, namely ethanol and itaconic acid. This was deemed of importance because renewable ethanol sources are required to replace environmentally unfriendly fossil-based fuels, while renewable itaconic acid could replace fossil-based industrial monomers if an economically viable source can be found. Emphasis was placed on optimising both yields (g/l) and substrate conversion, as a function of the theoretical maximum possible, for both compounds. The compositions of sorghum white bran (WB) and red bran (RB) were first elucidated to determine their suitability for downstream fermentation uses. Results revealed that the brans appeared to contain adequate components for biomass growth, with approximate carbohydrate, protein, lipid and ash contents of 69 %, 16 %, 3 %, 2 % and 70 %, 17 %, 4 %, 1 % found in WB and RB, respectively. Second, methods to obtain glucose-rich hydrolysates (for later use in fermentations) from the sorghum bran were investigated. It was found that amylolytic enzymes could produce enzyme hydrolysates (WBEH and RBEH) with glucose contents ranging from 48 g/l to 61 g/l. Alternatively, the brans could be digested to simple sugars using 3 % H2SO4 which converted up to 70.5 % of the bran into glucose, with dilute acid hydrolysates (WBDAH and RBDAH) having glucose contents ranging from 48 g/l - 57 g/l. Levels of the common fermentation inhibitors hydroxymethylfurfural, furaldehyde and vanillin were relatively low in all sorghum bran hydrolysates. Spot plate tests and phenotypic microarrays revealed that several yeast species metabolised and thrived on the hydrolysates. Ethanol mini-fermentations were successful with Kluyveromyces marxianus attaining the highest 88.9 % of theoretical maximum ethanol on RBEH, with other yeast strains also producing high yields. Production of itaconic acid by fermentation with 46 isolates of Aspergillus terreus was then attempted. Screening experiments on a defined glucose medium revealed that IA production levels were not normally distributed in nature. The highest producers were employed in 25 ml fermentation using the sorghum hydrolysates as a feedstock but the yields were found to be low compared to use of the defined glucose medium, with the highest yield (by isolate 49-22) being 5.5 g/l which corresponds to just 32.4 % conversion efficiency. Several approaches were therefore investigated to attempt to improve IA yields from A. terreus fermentations. Firstly, several hydrolysate purification techniques were attempted. The use of activated charcoal improved RBDAH yields very slightly, although most treatments resulted in lower IA yield. Secondly, ultraviolet mutagenesis was attempted using two high IA producing isolates, 49-22 and 49-5. Several promising mutants were obtained including one showing a 3.5-fold increase over the parent. However, these high yields could not be replicated in subsequent experiments. Thirdly, attempts were made to induce the sexual cycle of A. terreus in order to generate genetically diverse offspring that might include progeny with improved IA production. A molecular diagnostic was used to determine mating type and several isolates of opposite MAT were crossed in all possible combinations on three media under various temperature and gaseous exchange conditions. Hyphal masses containing cleistothecia, asci and ascospores were produced from two weeks onwards, which varied in number according to conditions and crossing partners. Most isolates were of low fertility, but 49-40, 49-43 and 49-44 were identified as “super-maters”. Sorghum flour agar (SFA) produced approximately seven times more structures than other agar media assayed, the effect of temperature varied according to media, whilst allowing gas exchange resulted in more hyphal masses than sealing the plates. Although asci containing 4-8 ascospores were identified, difficulties were encountered in obtaining viable ascospore offspring. Only one putative recombinant offspring was obtained, as evidenced by molecular verification using RAPD-PCR and MAT markers. This isolate exhibited low IA yields in fermentations. Finally, fermentation optimisations were performed using the response surface methodology approach. A half-factorial screening experiment was used to select three fermentation factors then a central composite design (CCD) performed to obtain the optimum conditions. Optimum conditions for IA fermentation using RBDAH as a feedstock were found to be 30 oC, pH 4.0 and an A. terreus inoculum of 1.0 x106 spores/ml, resulting in 13.5 g/l IA and 28.3 % of theoretical maximum possible conversion, representing a 2.45-fold increase over non-optimised values obtained in initial time-point experiments. Higher pH and inoculum sizes, with lower temperatures favoured IA formation. Scale up to fermentation volumes of 200 ml and 500 ml was performed and these also generated even higher yields of 13.9 g/l and 16.3 g/l IA, corresponding to 49.6 % and 46.1 % of theoretical maximum respectively. Overall, it was concluded that hydrolysates obtained from the wet-milling of sorghum bran can be used in the fermentative production of value-added chemicals with promising yields and efficiency, which warrants further research attention.